2020
DOI: 10.1177/1464420720944571
|View full text |Cite
|
Sign up to set email alerts
|

A review of stress concentration studies on fibre composite panels with holes/cutouts

Abstract: Composite panels are widely used as structural members due to their high strength-to-weight ratio. In order to reduce further weight, cutouts or notches are introduced in these members. These cutouts also serve utility requirements such as man-holes for purpose of service as well as for passing electric or fuel lines. An aircraft wing rib is a typical example of such a composite panel. Even while composites with holes or cutouts provide great savings in weight compared to metallic structures, the presence of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…[46] It was noted that increase in test temperature from 200 to 350 C increased the CoF of composites initially and then decreased. [47][48][49] In the current experiment, CGFs were adopted to manufacture epoxy-based composites and tribological analysis was done. CGFs were used in untreated, NaOH, and KMnO 4 treated conditions and the effects of chemical treatment on rate of wear, frictional force, and CoF were determined.…”
Section: Introductionmentioning
confidence: 99%
“…[46] It was noted that increase in test temperature from 200 to 350 C increased the CoF of composites initially and then decreased. [47][48][49] In the current experiment, CGFs were adopted to manufacture epoxy-based composites and tribological analysis was done. CGFs were used in untreated, NaOH, and KMnO 4 treated conditions and the effects of chemical treatment on rate of wear, frictional force, and CoF were determined.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional methods of repairing aluminum alloys, for instance, mechanical fastening, could lead to new defects. Composite patches, unlike traditional methods, do not cause any damage to the parent plate and can be replaced several times [ 1 , 2 , 3 , 4 , 5 , 6 ]. Fiber-reinforced polymer composites are the right choice for being used as a patch since these materials have a high stiffness-to-weight ratio, good fatigue resistance, and excellent corrosion resistance [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bash et al 53 reported buckling behavior of thin carbon/epoxy composite plates with rectangular cut-outs considering variation in position and number of cut-outs. The problem of stress and strain concentrations around cut-outs has been addressed by tailoring the panel in-plane stiffness by means of fiber-steered laminates, [54][55][56] cut-out reinforcement designs, 57 defense hole system, 58 etc.…”
Section: Introductionmentioning
confidence: 99%